ฐานบัวลูกแก้วอกไก่ของปราสาทในศิลปะขอมสมัยเมืองพระนคร - ภู่มาลี นงนุช (Journal of Fine and Applied Arts Khon Kaen University, 2014)
จากการศึกษาลวดบัวของฐานลูกแก้วอกไก่ในโบราณสถานศิลปะขอมสมัยเมืองพระนครนั้น อาจทำให้เชื่อได้ว่าน่าจะมีที่มาจากฐานบัวลูกแก้วขนาดใหญ่ที่ได้พบมาก่อนแล้วตั้งแต่สมัยก่อนเมืองพระนคร และอาจเริ่มประดิษฐ์ใช้ประดับตกแต่งชุดฐานของปราสาทขอมอย่างน้อยในศิลปะสมัยแปรรูป (ราวพ.ศ.1490-1510) โดยได้รับความนิยมอย่างมากในศิลปะสมัยปาปวน (ราวพ.ศ.1560-1630) ศิลปะสมัยนครวัด(ราวพ.ศ.1650-1720) เป็นต้นมา และฐานบัวลูกแก้วอกไก่อาจมีการกำหนดลำดับความสำคัญในการประดับตกแต่งส่วนสำคัญๆ ของศาสนสถาน เมื่อเทียบกับรูปแบบที่มีมาก่อนในศิลปะสมัยพะโคเช่นฐานบัวลูกฟัก ซึ่งใช้ประดับตกแต่งองค์ ประกอบอื่นๆ ของศาสนาสถานหนึ่งที่มีความสำคัญในลำดับรองลงมา The Pointed Torus Moulding Base in Khmer Ancient Remains of Angkor From the study of pointed torus moulding base in Khmer ancient remains of Angkor period, it is possible that those pointed torus mouldings originated from torus moulding found during Pre-Angkor period. The pointed torus moulding might had been invented and decorated at bases of Khmer sanctuaries at lease from Pre Rub (around 947-647 A.D.) and had become popular since Baphuon (around 1017-1087 A.D.) and Angkor Wat (around 1107-1177 A.D.) Also, it seems that the pointed torus moulding base had been identified to decorate only at the important positions of sanctuaries comparing to the previous style in Preah Ko, the lotus petal base for example, which it has been decorated at other less important positions in sanctuaries.